Mathematical Critical Thinking Skills Senior High School Student Based on Mathematical Resilience and Domicile - Ayu Faradillah; Tia Humaira (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2021)
The purpose of this study was to analyze students' mathematical critical thinking in terms of mathematical resilience and domicile. The method used in this research is descriptive qualitative where the process of selecting the subject uses an application called Winstep. Researchers used 473 high school students from 6 different schools to be the subjects in this study. The technique of taking the subject from research is based on the students' mathematical resilience level so there are 3 categories, namely high mathematical resilience, moderate mathematical resilience and high mathematical resilience. Data collection techniques using questionnaires, tests and interviews. Students are given a questionnaire in advance to determine the subject who will take the next test, namely mathematical critical thinking questions, after which the student's answers are analyzed and the researcher conducts interviews to find out how students solve the problems given and how many indicators the students can solve obtained in this study are students with high mathematical resilience obtain low critical thinking skills, students with moderate mathematical resilience acquire high critical thinking skills and students who have low mathematical resilience obtain moderate critical thinking skills.